How using aerial drones to deliver projects during Covid lockdown led to a 'new normal'. Issue 5 (16th February 2022) - Jefferies, Oliver; Farrow, John; James, Karl
Abstract : The paper illustrates how unmanned aerial vehicle surveys were used to support the refurbishment designs of seven rural bridges in Wales during a Covid-19 lockdown in 2020. The hundreds of high-resolution photos captured for each structure were used to produce photo-realistic three-dimensional photogrammetry models using automated processes. Although born of necessity, the reduction in cost, duration and disruption, together with the elimination of risks associated with conventional surveys show the case for wider adoption beyond the pandemic.